Vimbuza or Mashawe: mystic therapy - Chilivumbo, A. B. (International Library of African Music, 1972)
Malawi is remarkably rich in traditional dance varieties. In a country with a population less than a third that of New York or London City there are well over 60 different kinds of dances. Dancing, one might say, is a nerve centre of the rural Malawi life where it serves multi-functions. These functions range from joy to hate. People dance for both joy and grief. There is an array of dances for work; hate; prosperity; praise; socialisation and invitation; entertainment; grief and for healing. Some dances have multiple roles and functions such that one dance may serve different purposes to the dancers, the organisers and the spectators
Keywords: Ethnomusicology; Dance; Dance therapy; Malawi; African Music